PPARγ in Ischemia-Reperfusion Injury: Overview of the Biology and Therapy - Ruizhen Huang; Chiyu Zhang; Xing Wang; Honglin Hu (Frontiers Media S.A., 2021)
Ischemia-reperfusion injury (IRI) is a complex pathophysiological process that is often characterized as a blood circulation disorder caused due to various factors (such as traumatic shock, surgery, organ transplantation, burn, and thrombus). Severe metabolic dysregulation and tissue structure destruction are observed upon restoration of blood flow to the ischemic tissue. Theoretically, IRI can occur in various tissues and organs, including the kidney, liver, myocardium, and brain, among others. The advances made in research regarding restoring tissue perfusion in ischemic areas have been inadequate with regard to decreasing the mortality and infarct size associated with IRI. Hence, the clinical treatment of patients with severe IRI remains a thorny issue. Peroxisome proliferator-activated receptor γ (PPARγ) is a member of a superfamily of nuclear transcription factors activated by agonists and is a promising therapeutic target for ameliorating IRI. Therefore, this review focuses on the role of PPARγ in IRI. The protective effects of PPARγ, such as attenuating oxidative stress, inhibiting inflammatory responses, and antagonizing apoptosis, are described, envisaging certain therapeutic perspectives.